Historicizing the Bard of Avon: Shakeshifting Shakespeare and the Constitution of Guarati Literary Culture - Ashwinkumar, Hemang (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
In a century and a half of his continuous presence in India, Shakespeare has shapeshifted into manifold textual and performative “avatars,” from an agent of moral edification transforming into a subversive stick with which to beat the imperial culture. The “Bard” adapted to his immediate environs like a chameleon on the one hand, while standing tall on his native stage, on the other, asserting the imperial will and throwing the native cultural background in sharp relief. The Gujarati theatre and literary histories have borne witness to this ceaseless transformation. The present paper traces the high points in the histories of the “Bard’s” localization—from Shakespeare to Sheikh Pir—as well as his “non-localizations,” examining in the process how they reflect the evolution of the Gujarati literary culture along the caste, ethnic, and communal lines. An attempt is made in the paper to understand the role these histories could have played in engendering the essentialized, elitist, and monolithic ideas and identities that Gujarati literary culture still suffers from. Finally, the paper also points to the possible directions the translation and staging of Shakespeare’s plays can take in the postcolonial era.